Action APAC: understanding perceptions, attitudes and behaviours in obesity and its management across south and Southeast Asia - Tham, Kwang Wei; Ahmed, Asma; Boonyavarakul, Apussanee; Garcia, Mariana Mercado; Guajardo, Miroslava; Nor Hanipah, Zubaidah; Nam, Tran Quang; Nicodemus, Nemencio A.; Pathan, Faruque; Romano, Jack Garcia Uranga; Soegonda, Sidartawan; Tolentino, Edgardo L.; et al. (Wiley-Blackwell Publishing Ltd., 2024)
To identify perceptions and attitudes among people with obesity (PwO) and healthcare professionals (HCPs) toward obesity and its management in nine Asia-Pacific (APAC) countries, a cross-sectional online survey was conducted among adult PwO with self-reported body mass index of ≥25 kg/m2 (≥27 kg/m2, Singapore), and HCPs involved in direct patient care. In total, 10 429 PwO and 1901 HCPs completed the survey. Most PwO (68) and HCPs (84) agreed that obesity is a disease; however, a significant proportion of PwO (63) and HCPs (41) believed weight loss was the complete responsibility of PwO and only 43 of PwO discussed weight with an HCP in the prior 5 years. Most respondents acknowledged that weight loss would be extremely beneficial to PwO's overall health (PwO 76, HCPs 85), although nearly half (45) of PwO misperceived themselves as overweight or of normal weight. Obesity was perceived by PwO (58) and HCPs (53) to negatively impact PwO forming romantic relationships. HCPs cited PwOs' lack of interest (41) and poor motivation (37) to lose weight as top reasons for not discussing weight. Most PwO (65) preferred lifestyle changes over medications to lose weight. PwO and HCPs agreed that lack of exercise and unhealthy eating habits were the major barriers to weight loss. Our data highlights a discordance between the understanding of obesity as a disease and the actual behaviour and preferred approaches to manage it among PwO and HCPs. The study addresses a need to align these gaps to deliver optimal care for PwO. © 2024 The Authors. Clinical Obesity published by John Wiley & Sons Ltd on behalf of World Obesity Federation.